2015
DOI: 10.1155/2015/861849
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Lateral Epicondylitis: A Systematic Review

Abstract: Objective. This systematic review aimed to assess the effectiveness and safety of acupuncture for lateral epicondylitis (LE). Methods. Seven databases and the WHO International Clinical Trials Registry Platform Search Portal were searched to identify relevant studies. The data were extracted and assessed by two independent authors, and Review Manager Software (V.5.3) was used for data synthesis with effect estimate presented as standard mean difference (SMD) and mean difference (MD) with a 95% confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…However, current data from evidence-based medicine indicate conflicting results. Two systematic reviews have not concluded whether acupuncture was effective for LE [69,70], whereas three systematic reviews suggest that acupuncture is very effective in relieving LE pain in the short term, with the long-term results remaining unclear [71][72][73].…”
Section: Extracorporeal Shock-wavementioning
confidence: 99%
“…However, current data from evidence-based medicine indicate conflicting results. Two systematic reviews have not concluded whether acupuncture was effective for LE [69,70], whereas three systematic reviews suggest that acupuncture is very effective in relieving LE pain in the short term, with the long-term results remaining unclear [71][72][73].…”
Section: Extracorporeal Shock-wavementioning
confidence: 99%
“…All 6 trials included (see below) were of high quality and suggested that acupuncture was effective in providing short-term pain relief, with 5 out of 6 trials showing that acupuncture could be more effective than control treatment. In a more recent systematic review [117] with a total of four (see above) randomised controlled trials and 309 patients, no reliable statement could be drawn about the efficacy of acupuncture in lateral epicondylopathy due to the small number of cases and poor methodological quality of the trials.…”
Section: Acupuncturementioning
confidence: 99%
“…However, a 2015 systematic review of the effectiveness and safety of acupuncture for lateral epicondylitis was inconclusive due to the small number of studies with poor methodological quality [32].…”
Section: Strength Of Recommendation: Cmentioning
confidence: 99%